Production of glucose from oil palm foliages by using ammonia pretreatment - Tay, Qiao Rou, 1990-, author; Noraini Jaafar, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2013